Child Marriage in Canada. Issue 1 (8th January 2021) - Koski, Alissa; Clark, Shelley
Abstract: Child marriage, defined as formal or informal marriage before the age of 18, is a globally recognized indicator of gender inequality. Canada has placed itself at the forefront of global efforts to end child marriage as part of its commitment to the United Nations Sustainable Development Goals. Despite these global aspirations, child marriage remains legal throughout Canada. Data from vital statistics agencies and recent censuses indicate that child marriage, although rare, is practiced across the country. In 2016, nearly 2, 300 children between 15 and 17 years of age were in union, a prevalence of 0.2 percent. The vast majority (98 percent) of these were informal, common‐law unions. Demographic patterns of child marriage in Canada are similar to those observed in many low‐ and middle‐income countries. Girls were far more likely to be married as children than boys and typically wed much older spouses. There were marked differences in the prevalence of child marriage across the country, with the highest estimates found in Alberta, Manitoba, Saskatchewan, and the territories. These findings draw attention to the discrepancy between Canada's domestic law and its foreign policy. They also highlight thorny challenges inherent in efforts to eradicate this practice in Canada and elsewhere.